(untitled) (Journal of the College of Education for Women, 2019)
This paper highlights the main features of conjunctive adverbials and their occurrence in English academic prose. It accounts for the semantic roles of conjunctive adverbials, forms in which they are used, their positions within a sentence, and their frequency of occurrence in different registers with special reference to academic prose. It also tries to investigate possible differences in men’s and women’s use of conjunctive adverbials.Keyword: conjunctive adverbials, linking adverbials, stance adverbials, circumstance adverbials, academic prose